فاعلية برنامج تعليمي مقترح باستخدام طريقة "جيكسو" للتعلم التعاوني لتحسين مهارات الكتابة باللغة الانكليزية لدى طلبة الصف الأول الثانوي "دراسة تجريبية في مدارس مدينة اللاذقية الرسمية" (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى تقصي فاعلية برنامج تعليمي مقترح يستخدم أسلوب التعلم التعاوني "طريقة جيكسو" لتحسين مهارات الكتابة باللغة الإنكليزية من خلال مهارات التلخيص الكتابي للقصة القصيرة, ومهارات التلخيص الكتابي لنصوص القراءة, ومهارات كتابة موضوع الإنشاء, ولتحقيق أغراض البحث تمّ تقسيم عينة الدراسة إلى مجموعة تجريبية وعددها /75/ طالباً ومجموعة ضابطة وعددها /75/ طالباً, وانتهى البحث إلى النتائج التالية: - وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلاب في المجموعتين التجريبية والضابطة في مهارات التلخيص الكتابي للقصة القصيرةلصالح المجموعة التجريبية. - وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلاب في المجموعتين التجريبية والضابطة في مهارات التلخيص الكتابي لنصوص القراءة  لصالح المجموعة التجريبية. - وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلاب في المجموعتين التجريبية والضابطة في مهارات كتابة موضوع الإنشاء لصالح المجموعة التجريبية. This research aims at investigating the effectiveness of an educational programme based on the cooperative learning strategy (Jigsaw) for improve writing skills in English  through learning  summarizing skills of short stories, summarizing skills of reading texts, and writing skills in composition. To achieve the objectives of this research, the sample of this study is divided into an experimental group  consisting of /75/ students and a control group consisting  of /75 / students.  The results obtained are as follows: 1-There are  significant statistical differences between the control group's mean scores  and the experimental group's mean scores in the writing skills of summarizing a short story  in favor of the experimental group. 2-There are significant statistical differences between the control group's mean scores and the experimental group's mean scores in the writing skills of summarizing  reading texts in favor of  the experimental group. 3-There are significant statistical differences between the control group's mean scores and the experimental group's mean scores in the writing skills of composition in favor of the experimental group.